Implementation of Character Development through the Islamic Personal Development Program at Ishlahul Ummah Prabumulih IT High School - Sheilda Nurgenti; Ina Purnama Sari; Nida Parhanat; Dzakya Alya Khasanah; Zaqia Alfanirah Salsabilla; Gupran Ali Atas (al-Afkar, Journal For Islamic Studies, 2026)
This research is fucused on detailing how the Islamic Personal Development Program (BPI) is executed for character building based on religion at SMA IT ISHLAHUL UMMAH Prabumulih, while also pinpointing factors that help and hinder this process. The methodology empeloyed was a descriptive qualitative approach. To gather data, techniques included observing, conduting in-depth interviews with the principal, Islamic Religious Education instructors, and students, as well as reviewing documentation. For data analysis the Miles and Huberman framework was applied, incorporating steps like  data reduction, data presentation, and drawing conclusions. Findings reveal that the BPI program was successfully implemented based on three key components: daily religious activities, weekly mentoring sessions, and the discussion group known as "Ngobar" (Chatting Together). The success qdwof  this program was bolstered  by a supportive school atmosphere, sufficient facilities, and the impact of Islamic Religious Education teachers who serve as role models for students. Nevertheles, challenges arose  due to the varied religious backgrounds of the students and the  limited involvement of parents at home. The study concluded that collaboration  between schools and parents, combined with routine evaluation, is essential for sustaining  the consistency of students' religious character.